An analysis of students’ difficulties in learning vocabulary at secondary school in Muhamadiyah Waipare Maumere - AG, Moh Satryo; Janggo, Wendelinus Oscar; Yumelking, Marselus (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2024)
This study aimed to identify the challenges and variables that eighth-grade students encounter when learning vocabulary. A quantitative research design was used in this study. The researchers employed close-ended questionnaires as the data collection tool in conjunction with an indirect communication technique to obtain the data. The eighth-grade pupils were the focus of this study. All of the data underwent descriptive analysis. The results demonstrated that students had a variety of challenges when it came to learning vocabulary. Grammar is the main factor, but students also have trouble learning vocabulary because of pronunciation and meaning. Additionally, there are external and internal factors that affect how well students learn vocabulary. The internal components included development, IQ, experience, drive, and memory. The usage of learning media, school facilities, family, and a variety of teaching methods were the external factors. The solutions to these problems are to read a lot of English vocabulary, practice learning vocabulary through exercises, and cultivate enthusiasm and motivation for learning vocabulary.